Cost Analysis of Pulp Disease Treatment Using the Activity-Based Costing Method at XY Kajen Hospital - Gunarti, Gunarti; Suryawati, Chriswardani; Arso, Septo Pawelas (Sekolah Vokasi Universitas Gadjah Mada, 2025)
Background: Dental pulp disease was the case with the highest prevalence at the Dental Clinic of XY Kajen Hospital. The main constraint in root canal treatment was the high procedural cost, which led to low patient acceptability.Objective: This study aimed to analyze and calculate the unit cost of dental pulp disease treatment at the Dental Clinic of XY Kajen Hospital using the Activity-Based Costing (ABC) method as a basis for rational tariff determination. Additionally, a comparative analysis of the Cost Recovery Rate (CRR) was conducted among JKN tariffs, the Double Distribution (DD) method, and the ABC method.Methods: This study employed a field study design with a qualitative descriptive approach. Primary data were collected through direct observation, in-depth interviews, and documentation review, while secondary data were obtained from the hospital information system. Data analysis was conducted systematically through the stages of data reduction, data presentation, and conclusion verification.Results: Unit cost analysis using the ABC method showed that the current general tariffs were lower compared to the ABC calculation results, and for some types of procedures, they were even lower than the INA-CBGs tariff package. These findings indicated that there were cost components and cost drivers that had not been comprehensively calculated in conventional tariff setting. In response to the low INA-CBGs CRR, hospital management implemented a cost containment strategy for service operational cost efficiency.Conclusion: The ABC method proved to be a valid analytical instrument for cost evaluation and strategic tariff setting in hospitals, as it was able to present resource cost allocation more accurately and transparently compared to conventional methods.